Development and validation of a measure of concrete and abstract thinking - Hjördis Lorenz; Esther Beierl; Gabriella Tyson; Jennifer Wild (PLoS ONE, 2025)
Abstract-analytical thinking, which characterizes rumination and worry, has been shown to be a risk and maintenance factor for psychological disorders, yet there are no accessible, reliable measures that can be easily administered to assess this cognitive process. Student paramedics are at elevated risk of developing mental health difficulties associated with rumination and worry due to the nature of their work. The current study describes the development and validation of the Concrete and Abstract Thinking measure (CAT) in a sample of student paramedics. The scenario-based CAT measure was systematically developed. An initial pool of scenarios was generated based on previous research and the Worry Domains Questionnaire. A total of 14 paramedics, inclusive of student paramedics, evaluated the content of the scenarios. Final items were determined based on best-fit using confirmatory factor analysis. Two-hundred student paramedics completed the CAT measure and associated measures and 96.6% completed it again for test-retest reliability. Abstract items of the CAT measure showed good internal consistency (α=.87), test-retest reliability (ICC = .88) and good factorial, construct and criterion validity. The CAT measure was significantly associated with measures of perseverative thinking (r = .52), rumination (r = .42), worry (r = .50), depression (r = .32), anxiety (r = .41), posttraumatic stress disorder (r = .23), self-efficacy (r = -.32) and resilience (r = -.30). Overall, the CAT measure showed robust psychometric properties, evidencing good validity and reliability. The CAT measure offers a user-friendly, valid, reliable and population-specific measure of concrete and abstract thinking whilst also providing a model of how abstract thinking could be assessed in a range of populations at risk of developing mental health disorders.